Comparative Analysis of Performance of Honda Vario 125 Cc Motorcycle in 2022 Fueled by Pertalite, Pertamax, and Pertamax Turbo - Arnes Wildan Wahyudi; Moh Syaiful Anwar (Yayasan Adra Karima Hubbi, 2024)
This report presents a comparative analysis of Honda motorcycle performance using Pertalite, Pertamax and Pertamax Turbo fuels. The research was conducted through testing motorcycle performance under various conditions, including maximum speed, fuel consumption. The results show the performance differences between the two fuel types, providing valuable insights for consumers and Honda motorcycle manufacturers. The implications of these findings may influence the selection of fuels that suit the needs of everyday users and sustainable environmental policies.